High tissue glucose alters intersomitic blood vessels in zebrafish via methylglyoxal targeting the VEGF receptor signaling cascade - Jörgens, Kristina; Fleming, Thomas; Sticht, Carsten; Nawroth, Peter Paul; Hammes, Hans-Peter; Kroll, Jens (Diabetes, 2015)
Hyperglycemia causes micro- and macrovascular complications in diabetic patients. Elevated glucose concentrations lead to increased formation of the highly reactive dicarbonyl methylglyoxal (MG), yet the early consequences of MG for development of vascular complications in vivo are poorly understood. In this study, zebrafish were used as a model organism to analyze early vascular effects and mechanisms of MG in vivo. High tissue glucose increased MG concentrations in tg(fli:EGFP) zebrafish embryos and rapidly induced several additional malformed and uncoordinated blood vessel structures that originated out of existing intersomitic blood vessels (ISVs). However, larger blood vessels, including the dorsal aorta and common cardinal vein, were not affected. Expression silencing of MG-degrading enzyme glyoxalase (glo) 1 elevated MG concentrations and induced a similar vascular hyperbranching phenotype in zebrafish. MG enhanced phosphorylation of vascular endothelial growth factor (VEGF) receptor 2 and its downstream target Akt/protein kinase B (PKB). Pharmacological inhibitors for VEGF receptor 2 and Akt/PKB as well as MG scavenger aminoguanidine and glo1 activation prevented MG-induced hyperbranching of ISVs. Taken together, MG acts on smaller blood vessels in zebrafish via the VEGF receptor signaling cascade, thereby describing a new mechanism that can explain vascular complications under hyperglycemia and elevated MG concentrations.